Building the Character of a Community Concerned with Ecology through the Environmental Reforestation Program in Madiun City - Agus Prasetya; Ani Anjarwati; Suparti Suparti (Jurnal Penelitian Pendidikan IPA, 2024)
Environmental damage in urban areas is getting worse due to physical development, pollution from motorized vehicles, motorbikes and cars, and pollution and the lack of Green Open Space (RTH). Research gap in the context of this study, air pollution causes unhealthy urban environments, exhaust emissions from cars, motorbikes, dirty air, reduced oxygen (O2), causing hot air to minimal greenery. This study uses a qualitative research approach with descriptions in the form of narratives, stories, words to the subjects studied. Data collection methods through observation, in-depth interviews, and documentation, data sources are obtained from primary data, namely the community, while secondary sources are environmental NGOs, students, community leaders. Data analysis is carried out through the Interactive Miles and Huberman model which includes the stages of data collection, data reduction, data presentation, and drawing conclusions from data. To explore the data, researchers used the Social Construction Action theory study by L. Berger, T. Luckman, namely a theory that focuses on human social actions in social interaction. The results of the study indicate that a community construction process is needed in order to obtain social change in society, create environmental awareness, with large trees that produce O2.